The influences of the corporate governance on the accounting quality: Empirical evidence from the UK listed companies - YAO, Wang (2018)
The primary objective of the dissertation is to explore the empirical effects of corporate governance on the accounting quality in the UK listed market, aiming at preventing accounting fraud and boosting the quality of accounting information.